2002
DOI: 10.1103/physrevb.65.094105
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the solubility of Zr in Al

Abstract: The experimental solubility limit of Zr in Al is well-known. Al3Zr has a stable structure DO23 and a metastable one L12. Consequently there is a metastable solubility limit for which only few experimental data are available. The purpose of this study is to obtain by ab-initio calculations the solubility limit of Zr in Al for the stable as well as the metastable phase diagrams. The formation energies of several ordered compounds AlxZr (1−x) , all based on an fcc underlying lattice, were calculated using the FP-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 43 publications
8
54
0
Order By: Relevance
“…One should notice that these solubility limits have been found to be consistent with ab-initio calculations 25,30 and thus with the formation energies we used for Al 3 Zr and and Al 3 Sc.…”
Section: Atomic Model a Al-zr And Al-sc Thermodynamicssupporting
confidence: 87%
See 1 more Smart Citation
“…One should notice that these solubility limits have been found to be consistent with ab-initio calculations 25,30 and thus with the formation energies we used for Al 3 Zr and and Al 3 Sc.…”
Section: Atomic Model a Al-zr And Al-sc Thermodynamicssupporting
confidence: 87%
“…until Al melting temperature (T mel = 934K). For Al-Zr interactions, as we want to model precipitation of the metastable L1 2 structure of Al 3 Zr compound, we use the metastable solubility limit that we previously obtained from ab-initio calculations 25 , whereas for Al 3 Sc the L1 2 structure is stable and we use the solubility limit arising from a thermodynamic modelling of experimental data 32 :…”
Section: Atomic Model a Al-zr And Al-sc Thermodynamicsmentioning
confidence: 99%
“…Therefore, we have recalculated these quantities using his C ij values, and the method described in section 2.4. Similarly, we have calculated the polycrystalline elastic moduli of L1 2 -Al 3 Zr using the C ij values of Clouet et al [57]. From these quantities, the polycrystalline elastic moduli of the multicomponent L1 2 phase can be calculated with the assumption of linear superposition effect, which has been demonstrated to be a good approximation [59].…”
Section: Ab Initio Elastic Propertiesmentioning
confidence: 96%
“…With respect to the formation of the sub-stochiometric phase in the ¢A free region, we believe that the cooling rate has reduced to a point too low to form a supersaturated solid solution and that the solute concentration is too low to form the ¢A phase, favoring the formation of these precipitates. 12) In the case of the AlZr system, Clouet et al 32) have modeled the formation energy of several sub-stoichiometric Al-rich phases and found that the following compounds can be present: Al 4 Zr, Al 7 Zr, Al 8 Zr, Al 15 Zr and Al 31 Zr. It is worth mentioning that no experimental evidence was provided.…”
Section: ¹1mentioning
confidence: 99%